The Contribution of Nursing Specialists and Technicians to Patient-Centered Care in Primary Healthcare Facilities - Abdualaziz Eid Aealhamazani; Azizah Samet Al-Reshidi; Ashwaq Salh Alanazi; Alanoud Menwer Marzouq Alhamzani; Bushra Awad Maleh Alshammary; Naimah Badi Rashed Alshammari; Haya Mutni Muqbil Alanazi; Ashwaq Odhayb Khulaif Alshhammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The healthcare approach known as patient-centered care (PCC) incorporates the patient’s values, needs, and choices into the treatment process. It covers things like professionalism in the interactions between patients and medical professionals, which, if followed, have a favorable relationship with patients’ health, contentment, and successful quality of life. Aim of work: To explore the contribution of nursing specialists and technicians to patient-centered care in primary healthcare facilities. Methods: We conducted a comprehensive search in the MEDLINE database’s electronic literature using the following search terms: Contribution, Nursing Specialists, Technicians, Patient-Centered Care, and Primary Healthcare Facilities. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:In summary, the nursing specialists and technicians are crucial to patient focused care in primary health care structures. They not only enhance the quality of patient care delivery, establish supportive and inclusive healthcare context that acknowledges and incorporates every person’s experience of illness. Such contributions reflect the values of the modern approaches to primary care institutions focused on the availability, individuality, and proactivity.